Innovation in preregistration midwifery education: Web based interactive storytelling learning. (July 2017) - Scamell, Mandie; Hanley, Thomas
Abstract: Background: through a critical description of the implementation of a web based interactive storytelling learning activity introduced into an undergraduate, preregistration midwifery education programme, this paper will explore how low-cost, low-fidelity online storytelling, designed using Moodle, can be used to enhance students' understanding of compassion and empathy in practice. Sample: cross sectional sample of first year undergraduate Midwifery students (n111) Method: drawing from both research and audit data collected in an Higher Education Institution in London England, the paper presents the case for using web based technology to create a sustainable model for midwifery education. Findings: initial results indicate that it is both the low cost and positive student evaluations of web based interactive storytelling, which make this approach to preregistration midwifery education which suggests that this approach has significant potential for learning and teaching in midwifery education in diverse settings around the world. Or how about: global relevance? . Highlights: Embracing technology to create a sustainable midwifery education model Learning compassion and empathy through web based simulated midwifery practice Implementation of low cost, low fidelity web based interactive storytelling in preregistration midwifery education